Constitutional and Confusional Syndromes as A Form of Presentation of Disseminated Tuberculosis: Case Repo (Revista de Medicina Clinica, 2021)
Tuberculosis has become an emerging disease in the West, in parallel with the rising increase in migration from endemic countries, the internationalization of travelers, as well as the epidemic of the human immunodeficiency virus (HIV) and the growing use of immunosuppressive drugs.        The clinical presentation is usually insidious and highly varied, with frequently negative microbiological tests; which makes the diagnosis difficult on many occasions.
Keywords: Tuberculosis; Confusional syndrome; constitutional syndrome